Implementasi Kurikulum 2013 Mata Pelajaran Penjasorkes di Sekolah Pengembangan dan Percontohan - Putra, Yan Sonyardhi; Qoriah, Anirotul (Department of Physical Education, Sport, Health and Recreation, 2016)
This research aims to understand the implementation of curriculum 2013 on subject Penjasorkesin SMA Negeri 1 Batang and SMA Negeri 2 Batang 2014/ 2015. This research uses aqualitative approach that gives description about actual facts in the field work. The result ofthis research shows that based on qualitative descriptive analysis, 2 schools have operated theduty and capacity as the developing and sequential school quite well. Target of this research isthe implementation of curriculum 2013, school’s promptness, learning support, and responsesof executants in school. Some findings of this research are teachers and students have notreceived comprehensive handbook of curriculum 2013 from Kemendikbud. Teachers both inSMA Negeri 1 Batang and SMA Negeri 2 Batang have received sample of syllabus and validRPP from Kemendikbud. The implementation of scientific learning is still having problem;students seem to be less confident to show their ability in sports to their friends, sometimesteachers cannot move on from KTSP while learning process is happening, too many aspectsfor teachers processing the score, and the extension hour worsens them who have exercise classin the afternoon.